Demographic differences in healthy food purchases in a corner store intervention. Issue 4 (2nd October 2018) - Tibbits, Melissa; Wang, Hongmei; Soliman, Ghada; Schram, Sarah; Balluff, Mary; Grimm, Brandon L.; Siahpush, Mohammad
ABSTRACT: The aims of the current study were to examine the availability and customer purchases of five types of healthy foods promoted through a corner store intervention and to examine the association between healthy food purchases and age, gender, race/ethnicity, and receipt and use of WIC or SNAP benefits. Intercept surveys were conducted with 532 corner store customers. Most customers thought it was easy to find healthy food within the corner stores, but only 48% purchased at least one type of healthy food. Females, individuals who used WIC/SNAP benefits for their purchase, and Hispanics/Latinos had the highest probability of purchasing at least one type of healthy food. Implications for tailoring corner store interventions to different populations are discussed.